Rodent-Borne Orthohantaviruses in Vietnam, Madagascar and Japan - Fuka Kikuchi; Kae Senoo; Satoru Arai; Kimiyuki Tsuchiya; Nguyễn Trường Sơn; Masaharu Motokawa; Marie Claudine Ranorosoa; Saw Bawm; Kyaw San Lin; Hitoshi Suzuki; Akira Unno; Keisuke Nakata; et al. (Viruses, 2021)
Hantaviruses are harbored by multiple small mammal species in Asia, Europe, Africa, and the Americas. To ascertain the geographic distribution and virus-host relationships of rodent-borne hantaviruses in Japan, Vietnam, Myanmar, and Madagascar, RNA later ™-preserved lung tissues of 981 rodents representing 40 species, collected in 2011–2017, were analyzed for hantavirus RNA by RT-PCR. Our data showed Hantaan orthohantavirus Da Bie Shan strain in the Chinese white-bellied rat ( Niviventer confucianus ) in Vietnam, Thailand; orthohantavirus Anjo strain in the black rat ( Rattus rattus ) in Madagascar; and Puumala orthohantavirus Hokkaido strain in the grey-sided vole ( Myodes rufocanus ) in Japan. The Hokkaido strain of Puumala virus was also detected in the large Japanese field mouse ( Apodemus speciosus ) and small Japanese field mouse ( Apodemus argenteus ), with evidence of host-switching as determined by co-phylogeny mapping.